Paraganglioma of the spermatic cord. Report of a case with immunohistochemical and ultrastructural studies - Bacchi, C. E.; Schmidt, R. A.; Brandao, M.; Scapulatempo, R.; Costa, J. C.M.; Schmitt, F. C. (My University, 1990)
We describe a case of paraganglioma arising in the spermatic cord, which is an extremely rare location. Immunohistochemical studies characterized two types of cells: (1) polygonal cells expressing neuron-specific enolase, chromogranin A, and synaptophysin and (2) S100 protein-positive sustentacular cells. Electron microscopy revealed that within the cytoplasm of the polygonal cells, there were electron-dense granules whose morphological appearance was consistent with that of neurosecretory granules. Paraganglioma of the spermatic cord may originate from embryonic chromaffin cells that have followed the testis into the scrotum.